The Kampung Eco Briquette (Kang Ebit) Program as a Community-Based Circular Economy Model for Siwalan Waste Utilization in Kapu Village, Tuban Regency - Lingga Gayuh Kinara (Prospect Publishing, 2026)
Tuban Regency is one of the largest producers of palmyra palm (Borassus flabellifer) in East Java, Indonesia, generating substantial amounts of biomass waste, particularly palmyra shells, which remain underutilized. This community service program aimed to analyze the implementation of a community-based circular economy through the Eco Briquette Village Program in Kapu Village, which converts palmyra shell and coconut shell waste into environmentally friendly briquettes. The program was implemented using a community empowerment approach based on local potential, through social mapping, community capacity building through technical and business management training, the provision of production facilities, and continuous mentoring to strengthen local institutions and expand market access. The program introduced a social innovation called PESILAT (Integrated Palmyra Waste Processing), which uses pyrolysis technology and a dynamo-powered extruder. The implementation results showed that the program increased participants' average monthly income by approximately IDR 1.2 million while processing around 100 tons of biomass waste, equivalent to approximately 25% of the palmyra waste generated in the area. In addition to producing briquettes as an alternative renewable energy source, the production process also generated biochar and liquid smoke as value-added by-products. These findings demonstrate that community-based biomass utilization can enhance local economic empowerment while supporting sustainable environmental management.